PENGARUH FINANCIAL LEVERAGE TERHADAP TAX AVOIDANCE DENGAN KEPEMILIKAN MANAJERIAL SEBAGAI VARIABEL PEMODERASI - Kristin Natalin; Tatik Zulaika; Rosel Rosel (Balance: Media Informasi Akuntansi dan Keuangan, 2022)
The purpose of this research is to find out how much influence financial leverage on tax avoidance with Kepemilikan Manajerial as a moderating variable. The object of research used in this study is LQ45 companies listed on the Indonesia Stock Exchange (IDX) in 2016-2019. The sample selection method uses purposive sampling. The number of samples in this study were 68 samples from 17 companies that fit the sample criteria. Hypothesis testing is done by using moderated Regression analysis processed using SPSS software version 24. The results of this study indicate that financial leverage has a positive effect on tax avoidance. and kepemilikan manajerial reinforces the negative effect of financial leverage on tax avoidance